Fc-Gamma Receptor 3B Copy Number Variation Is Not a Risk Factor for Behçet's Disease. (30th May 2012) - Black, Rachel; Lester, Sue; Dunstan, Emma; Shahram, Farhad; Nadji, Abdolhadi; Bayat, Noushin; Saeedfar, Kayvan; Ziaei, Naghmeh; Hill, Catherine; Rischmueller, Maureen; Davatchi, Fereydoun
Abstract : Behçet's disease (BD) is an immune-mediated systemic vasculitis associated with HLAB51. Other gene associations are likely and may provide further insight into the pathogenesis of this disease. Fc-gamma receptors play an important role in regulating immune function. Copy number variation (CNV) of the Fc-gamma receptor 3B (FCGR3B) gene is associated with other inflammatory conditions and may also play a role in BD. The aim of this study was to determine whether CNV of the FCGR3B gene is associated with BD or its clinical features. FCGR3B copy number was determined for 187 Iranian patients and 178 ethnicity-matched controls using quantitative real-time PCR. The genotype frequencies were comparable in both BD patients and controls. The odds ratio for low copy number (<2CN) was 0.6 (P = 0.16 ) and the odds ratio for high copy number (>2CN) was 0.75 (P = 0.50 ). There was no association found between high or low CN of the FCGR3B gene and BD or its clinical features in this Iranian population. We are the first to report this finding which, when looked at in the context of other genetic studies, gives us further insight into the complex pathogenesis of BD.